Verletzungsrisiko, Überlastungsbeschwerden und prophylaktische Möglichkeiten beim Skilanglauf - Frank, B. C. (Sportverletzung Sportschaden, 1995)
A standardised questionnaire was drawn up and submitted to 690 cross-country skiers active in popular (pastime) sports, competitive sports and high-performance sports, between 1990 and 1993, covering a total of 189 injuries and 1,281 cases of complaints caused by overstrain. Over and above this, muscular imbalance and postural characteristics (for example, signs of vestibular syndrome) were examined in 94 of these skiers. Three times as many skiers (69.3%) reported on complaints than skiers reporting on injuries (20.3%). Complaints concerned particularly the lower extremities (45.9%), whereas injuries were more frequent at the upper extremities (47.6%). Minor injuries predominated (77%) such as sprains and distortions (23.8%), contusions (25.9%), skin injuries (13.7%) and muscle injuries (13.7%) as well as mild complaints (45.1%) such as blisters at the hand and feet. High-performance sportsmen (14.4%) are significantly most frequently injured when employing the skating technique, whereas in competitive sports the "classical" technique results in a greater incidence of accidents (16.1%). Most accidents occur during downhill skiing, on rutty and icy tracks, collisions, due to inadequate technique, lack of balance and unskilled handling. Complaints are significantly reported by competitive (70.8%) and high-performance sports people (74.8%) for both techniques. Whereas complaints at the lower extremities occur more often during skating technique (56.8%) than during the classical technique (34.5%), complaints concerning the trunk are seen more often with the classical technique (29.7%) than with the skating technique (8.9%). Complaints are caused by icy, rutty tracks, inadequate equipment, deficient training, muscular imbalances and previous damage. A large number of pointers on how to avoid pitfalls when employing the skating and classical techniques can be obtained via analysis of the injuries and complaints.